Combating homelessness: Insights from a homeless population - Syazwani Drani,; Azlinda Azman,; Paramjit Singh Jamir Singh, (Penerbit Universiti Kebangsaan Malaysia, 2020)
There are adequate discussions in literatures to define and discuss homelessness and the homeless. One definition of a homeless is an individual who does not have a permanent dwelling, but live on the streets or at shelters as temporary arrangements. Homelessness is due to several factors, which is also adequately discussed in the literatures. Being homeless, usually gives a negative perception on the wellbeing and social functionality of the homeless individual. This study aims to understand the pertinent issues from the perspective of the homeless. Primary data for this qualitative study were gathered through in-depth interviews of 20 homeless respondents in Penang. The study findings indicate that the underlying causes of homelessness are varied with the main ones being financial and family problems; and alcohol and drug related. Addressing these underlying causes is best way to address the homelessness problem in a more sustainable manner. Some strategies to reduce the number of homeless population based on the study include to better coordinate distribution of free food to reduce overdependence by the homeless, free housing if the case merits it and finally the need for more professional or qualified social workers who can work more closely with the population to empower them to lead a normal life and be less dependent on free handouts.